2011
DOI: 10.3340/jkns.2011.49.5.302
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Intramedullary Schwannoma Accompanying by Extramedullary Beads-Like Daughter Schwanommas

Abstract: Thoracic intramedullary schwannomas are rare spinal cord tumors. Most of these tumors have been reported as a single lesion in the spinal cord. The authors report the first case of intramedullary schwannoma accompanying by extramedullary beads-like daughter masses of the thoracic spine. A 68-year-old male presented with walking disturbance and decreased sensation below T10 dermatome. Imaging workup revealed an intramedullary mass at T6 and T7. T6 and T7 laminectomy and mass removal were performed. Intraoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Surgical excision of intramedullary schwannomas differs widely from extramedullary schwannomas. However, total excision may not be possible in all the cases, due to the adherence of the tumor to the surrounding neural tissue, 8 as in our case. Reoperation should be considered in case of recurence.…”
Section: Discussionmentioning
confidence: 77%
“…Surgical excision of intramedullary schwannomas differs widely from extramedullary schwannomas. However, total excision may not be possible in all the cases, due to the adherence of the tumor to the surrounding neural tissue, 8 as in our case. Reoperation should be considered in case of recurence.…”
Section: Discussionmentioning
confidence: 77%
“…Although some association of proliferating vessels around the tumour [4,32,35,68,102], tumour connection to a nerve root [4,27,34,43,46,52,58,68,71,76,77,84,89,99,104,107,109,115,123] or chronic disease of the spinal cord could be observed in reported cases [39,100,107], it is still not possible to make a general statement regarding the pathogenesis of IMS. In our case, a tumour connection to the nerve root could be observed in the MRI of the cervical spine.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, several authors did a literature review of intramedullary schwannomas since We have found that 48 cases were reported since 2005, which brings the total number of cases to 118, including our case. [1][2][3]8,10,11,13,18,19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The cases reported between 2005 and 2014 are summarized in ►Tables 1 and 2. Lee et al studied 10 cases of intramedullary schwannomas that were diagnosed in their hospital from 1995 to 2010 and they found that 7 of them were in the lumber region and 3 in the cervical regions.…”
Section: Discussionmentioning
confidence: 99%